Modification of energy bandgap in lattice mismatched InGaAs/GaAs heterostructures - Gelczuk, Łukasz; Dąbrowska-Szata, Maria (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
This paper addresses some physical aspects and presents experimental results concerning to phenomena which evoke modification of band structure in lattice mismatched InGaAs/GaAs heterostructures, namely the introduction of extra deep-lying energy levels in the bandgap. The deep level transient spectroscopy reveals commonly observed deep level defects in GaAs-based structures associated with native point defects as well as misfit dislocations related to strain relaxation processes.
Optica Applicata, Vol. 39, 2009, nr 4, s. 845-852
Keywords: optyka; bandgap energy; lattice mismatch; deep level defects; InGaAs heterostructures; deep level transient spectroscopy (DLTS)